NEW BUSINESS IDEA IN THE NEW NORMAL TIME - Hari Setiawan Saragih; Zuhrinal M Nawawi (International Journal Labs, 2022)
This research is focused on New Business Ideas in the New Normal Period, especially in the Pematangsiantar Town. The method used in this research is a qualitative approach model with an observational research design and literature study. The results from research and data processing show that business ideas with small capital during the new normal that can be realized include businesses in the food and beverage sector, home business, cosmetic and skincare business, health protocol equipment business, sports equipment business, and online grocery business. . This is of course a well-designed business plan arrangement and well-considered the level of risk, the level of complexity, and the scale of the business by the business actors